Peran Content Planner Pada Media Project @Ruangmagang.id - Aldawiyah, Siti; Syah, Firman; Wardhani, Annisa (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2025)
With the rise of digitalization trends and the important role of social media in modern communication, understanding the role of content planners has become increasingly vital. The MICE world faces significant dynamics, especially in dealing with the need for relevant and engaging content planning to establish connections with diverse audiences. The purpose of this study is how the process of creating a content plan on Instagram @ruangmagang.id. The method used is qualitative research. Content Plan Process @ruangmagang.id, This process begins with the analysis of the target audience, followed by the search for relevant content topics and the determination of the content delivery concept. There is an emphasis on the intensity of discussion and deliberation within the team, which results in content drafts that are in accordance with the ideas of team members and company directives. Suggestions for future authors to conduct further research on the concrete impact of changing an Instagram account to a business on increasing brand awareness, by analyzing the data and statistics obtained after the change is made. Keyword: role, content planner, media project